Materi Pembelajaran Tari Pendidikan untuk Sekolah Menengah Berbasis TIK dan CTL Bagi Mahasiswa - Oktarini, Selly (Program Studi Pendidikan Tari FBS UNJ, 2022)
Dance Education is one of the subjects that must be taken in the Dance Education Study Program undergraduate program. The purpose of this study is to bridge and support the achievement of student learning in the practice of Educational Dance in Middle Schools. Students will be trained, guided and provided with educational dance learning materials for ICT and CTL-based secondary schools. This research and development was carried out using the Research and Development (R&D) method with the Borg and Gall (2003) model. In conducting this research the creativity of students and students will be stimulated through exploration, improvisation to find dance forms which are the result of this exploration and improvisation using ICT and CTL learning models, either through property, music and visuals. Learning with a Contextual Teaching and Learning (CTL) learning model for students and students is not just sitting, listening and taking notes, but learning here is a process of experiencing directly. The process of full student involvement in finding the material they are learning and relating it to real life situations is an important thing, so that students are encouraged to be able to apply it in their lives. The teacher's role here is as a facilitator, a mediator who creates a conducive situation for the construction of knowledge in students.